Förtroendet för drivningsplanerarens arbete bland skogsmaskinförare - Alkberg, Johan (SLU/School for Forest Management, 2016)
The purpose of this study was to examine the confidence among forest machine operators concerning the performance of the cutting planners. There is a need to investigate the reasons behind and the possible solutions for, the lack of trust between these two groups. Forest machine operators in Ockelbo municipality where interviewed in October 2015. The machine operators were asked to subjectively grade their level of trust on a scale of 1 to 10 were 1 was the lowest and 10 was the highest. The results showed the machine operators trust in the cutting planners averaged 6.9. The machine operators expressed a clear preference for cutting planners who had practical experience operating a forest machine.